Rancang Bangun Media Pembelajaran Berbasis Android Smart NoteBook Digital Matematika - Ririn Febriyanti; Slamet Boediono (Musamus Journal of Mathematics Education, 2023)
This study aims to determine the development process and practicality of mathematics learning media with measurement materials (time, angle, distance and speed) in producing products in the form of android-based mathematics learning media through the ISpring application for Class V at SD Ganggantingan Kab. Lamongan. This research is motivated by students' interest in smartphones rather than teacher explanations in the classroom and the lack of student activity in participating during the learning process. The research method used in this research is Research and Development (R&D) by going through the stages of the ADDIE model, namely analysis, design, development, evaluation. Instruments used Questionnaire sheets consist of three types, namely questionnaires for material experts, media experts, students and teachers. Analysis of the data in this study in the form of descriptive analysis of the quality of learning media development with measurement materials. The results of the study show that the assessment of Smart NoteBook with time, distance and speed measurement materials is as follows: For the assessment carried out by material experts, the percentage is 84% in the very valid category, while the assessment carried out by media experts is 90% in the very valid category. . For practicality trials, this learning media obtained an average of 45.6 in the range of 40.8 < R 50.4 so it was categorized as practical. So it can be said that the learning media based on the Smart NoteBook Digital Mathematics can be used for class V Elementary School.